2017
DOI: 10.1587/elex.14.20170463
|View full text |Cite
|
Sign up to set email alerts
|

Research of circuit breaker intelligent fault diagnosis method based on double clustering

Abstract: According to the energy variation of the mechanical transmission in the process of circuit breaker operation which is characterized by acoustic and vibration signals, a new method of high Voltage circuit breaker mechanical fault diagnosis was proposed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…After years of development, clustering has many applications in fault identification. [12][13][14] Clustering has developed a variety of clustering methods for different scenarios. 15 In the study of dynamics research, due to the complexity of modal parameters, it is very difficult to determine the number of clustering groups in advance, so the fast clustering method that does not need to determine the number of clusters in advance is what we need.…”
Section: Principle Of Machine Tool Modal Classification Analysis Methmentioning
confidence: 99%
“…After years of development, clustering has many applications in fault identification. [12][13][14] Clustering has developed a variety of clustering methods for different scenarios. 15 In the study of dynamics research, due to the complexity of modal parameters, it is very difficult to determine the number of clustering groups in advance, so the fast clustering method that does not need to determine the number of clusters in advance is what we need.…”
Section: Principle Of Machine Tool Modal Classification Analysis Methmentioning
confidence: 99%
“…Then, the product functions were quantized by the approximate entropy, and the entropy value was taken as the characteristic of the fault signal. The result in [13] showed that the feature recognition accuracy extracted by double clustering is significantly higher than that of a single clustering method. Although the features extracted by the entropy as a characteristic attribute have certain characterization ability, the influence of disturbance and noise cannot be avoided, especially the statistic that directly quantizes the time series, such as the sample entropy, the permutation entropy, and the approximate entropy.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the energy entropy from the time domain and the frequency domain was extracted to construct the timefrequency entropy, and the one-class support vector machine (OCSVM) was used to determine whether there are mechanical failures or not. He et al [13] proposed a new method for the fault identification of high-voltage circuit breakers based on the density peak clustering, the kernel fuzzy C-means clustering and the support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…Literature [10] uses complementary ensemble empirical mode decomposition (CEEMD) algorithm to decompose sound-vibration signals and extracts the energy coefficient, sample entropy and power spectral entropy of IMF components as feature vectors for fault diagnosis. Literature [11] uses fuzzy peak optimization C-means clustering and SVM to diagnose sound-vibration signals. Although the above methods have achieved some achievements, there are still some existing problems:…”
Section: Introductionmentioning
confidence: 99%